The Level of Understanding of Accounting is Seen from the Educational Background and Learning Behavior - Dudung Ma’ruf Nuris; Vera Handayani (Future Science, 2021)
This study aims to examine whether there is an influence of educational background and learning behavior on the level of understanding of accounting. Understanding the basic concepts of accounting is the main key to assessing the success of learning in the field of accounting. If it is related to the learning process to gain a good understanding of accounting, then the accounting learning experience of students gained during previous education is very important that can be seen from the background of secondary education. Many factors affect the understanding of a student's accounting in addition to secondary education background factors, namely student learning behavior. Good learning behavior will have an impact on understanding good accounting concepts. This type of research is quantitative explanatory. Data collection tools use questionnaires and settings. Data analysis techniques used descriptive analysis and multiple linear regression analysis. The results showed that there was an influence of educational background on the level of understanding of accounting, and there was an influence of learning behavior on the level of accounting understanding. Accounting understanding is obtained from the interaction of various factors that influence it, both from internal factors and from external factors.